Effects of Short-Term Practice With a Tonic Drone Accompaniment on Middle and High School Violin and Viola Intonation. Issue 1 (July 2019) - Zabanal, John-Rine A.
The purpose of this study was to investigate the effect of tonic drone accompaniment on the intonation of violinists and violists. Twenty-eight middle and high school students performed an ascending diatonic line and a descending dominant 7th arpeggio on the violin or viola in three trials: pretest, posttest accompanied with drone, and posttest unaccompanied. The students were grouped based on age and years of experience. A significant difference in cent deviation scores was found between age groups but not years of experience. Post hoc analysis revealed a significant difference between the middle-age group and the youngest group. No significant difference was found overall between pretest, drone accompanied posttest, and unaccompanied posttest conditions.